Improving Elementary School Students' Understanding of Literacy and Numeracy Through Digital Applications - Hikamudin, Eviana; Riyadi, Arie Rakhmat; Aryanti; Peniasiani, Dian; Nuryani, Pupun; Gofur, Ridwan (MIMBAR PGSD Undiksha, 2023)
The challenges of changing times require individuals to have adaptive life skills. Literacy and numeracy skills are two general skills that students need to have. The research aims to analyze elementary school (SD) students' understanding of literacy and numeracy through the use of digital applications in learning. Data collection was carried out through survey techniques using questionnaires, observations, and interviews. The participants in this study were 177 grade 4 (four) elementary school students, four teachers, and two school principals. Processing and analysis of data using descriptive quantitative analysis by combining the results of interviews and observations using a comprehensive analysis technique. The results showed that students' understanding of literacy material reached 39.32, and numeration material reached 34.81. On other aspects, based on the observation of the implementation of learning, it was found that 91% of teachers had delivered literacy and numeracy material in the excellent category. Based on the interviews and field observations, data was obtained that all sample schools had literacy and numeracy strengthening programs and carried them out regularly at school. Strengthening literacy and numeracy using digital application assistance in assessments in schools is currently unable to increase students' understanding of literacy and numeracy significantly.